A simple and low‐cost active dual‐axis solar tracker. Issue 5 (23rd September 2018) - Hammoumi, Aboubakr El; Motahhir, Saad; Ghzizal, Abdelaziz El; Chalh, Abdelilah; Derouich, Aziz
Abstract: This paper presents the design and practical implementation of a simple active dual‐axis solar tracker (DAST) to track the sun's movement by using fewer components and low‐cost as well. A dual‐axis mechanism is developed in order to tilt the PV panel by two servo motors facing the highest intensity of sunlight captured by LDR sensors, which are placed in the four corners of PV panel. The DAST prototype was constructed practically and tested using a real‐time virtual instrument based on Excel to determine its efficiency. Moreover, a comparison based on experimental results between the energy produced by the proposed smart DAST and a fixed panel shows that the smart DAST produces 36.26% more energy compared to the fixed panel. The proposed active DAST can be easily implemented without possessing deep knowledge about solar tracking technologies and electronic engineering. Abstract : This paper presents the design, implementation, and test of a low‐cost smart active dual‐axis solar tracker (DAST). The proposed active DAST can be easily implemented without possessing deep knowledge about solar tracking technologies and electronic engineering.